A new species of Chlorophorus Chevrolat (Coleoptera: Cerambycidae: Cerambycinae) from China with description of biology - Zong, Shi-Xiang; Xie, Guang-Lin; Wang, Wen-Kai; Luo, Youqing; Cao, Chuan-Jian (Zootaxa, 2012)
The morphological and biological characteristics of the new species, Chlorophorus caragana sp. nov. from China, aredescribed. This new species is a serious pest of Caragana korshinskii Kom. in Ningxia Hui Autonomous Region, China.A key to the Chlorophorus species that occur in northern China is presented. The type specimens are deposited in the Entomological Museum of Yangtze University.